Implementasi Syariat Islam dan Strategi Dakwah: Studi terhadap Peran Pemerintah dan Lembaga Keagamaan di Aceh - Mohd Reza Pahlevi; Fakhrul Husni; Ramazana (Pawarta: Journal of Communication and Da'wah, 2025)
Islamic preaching and Sharia law are important instruments in realizing a society that is in accordance with Islamic values. In the province of Aceh, Islamic preaching serves as the spiritual and intellectual foundation for supporting the comprehensive implementation of Sharia law. This study aims to identify the role of the government and religious institutions in strengthening da'wah (proselytizing) and the role of the Aceh government in supporting the implementation of a holistic Islamic sharia based on local wisdom. The research method used was a descriptive qualitative method. Data was sourced from observation, interviews, and documentation. Dakwah in Aceh is a socially and religiously integrated system, structurally and culturally, involving collaboration between the government, religious institutions, and the community. The Aceh government plays a central role in implementing Islamic law through various regulations and strategic programs such as Border Da'i, Jinayat Training, and strengthening the practice of worship. However, the implementation of Islamic law still faces multiple obstacles, so synergy and sustained commitment from all elements are needed to ensure that Islamic law is fully realized. Dakwah in Aceh is an integral part of implementing Islamic law, involving synergy among the government, religious institutions, and the general public. The government of Aceh itself plays a crucial role in the implementation of Islamic Sharia law, from policy-making to the actual implementation of Sharia programs. Although many strategic programs have been implemented, their execution still faces various challenges, making cross-sectoral collaboration essential to achieve a comprehensive implementation of Islamic Sharia law in the daily lives of the people of Aceh, known as the “Bumi Serambi Mekkah.”